Toxic Parenting dan Implikasinya Terhadap Emosi Anak Usia Dini: Studi Kasus di Desa Jeruk Legi, Sidoarjo - Yusril, Muhammad; Yusuf, Ali (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2025)
This study aims to analyze the implications of toxic parenting on the emotions of early childhood in Desa Jeruk Legi, Sidoarjo. Toxic parenting refers to negative parenting patterns, including excessive criticism, strict control, emotional neglect, as well as verbal and physical abuse, which potentially hinder children's emotional development. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews with parents and children, participatory observations in family environments, and document analysis related to parenting patterns and children's emotional conditions. This study concludes that toxic parenting significantly negatively impacts the emotional development of early childhood. The suggested recommendations include organizing parenting education programs for parents, enhancing the role of schools in providing psychosocial support for children, and formulating government policies that promote a safer and healthier parenting environment Keywords: toxic parenting, early childhood emotions, parenting patterns.